Intensive Care and Organ Support Related Mortality in Patients With COVID-19: A Systematic Review and Meta-Analysis - Abhimanyu Chandel, MD; Sahar Leazer, MD; Karl C. Alcover, PhD; Josiah Farley, BS; Joshua Berk, BA; Christopher Jayne, BS; Ryan Mcnutt, BS; Meredith Olsen, MD; Rhonda Allard, MLIS; Jiahong Yang, BS; Caitlyn Johnson, BS; Ananya Tripathi, BS; et al. (Critical Care Explorations, 2023)
OBJECTIVES:. To perform a systematic review and meta-analysis to generate estimates of mortality in patients with COVID-19 that required hospitalization, ICU admission, and organ support. DATA SOURCES:. A systematic search of PubMed, Embase, and the Cochrane databases was conducted up to December 31, 2021. STUDY SELECTION:. Previously peer-reviewed observational studies that reported ICU, mechanical ventilation (MV), renal replacement therapy (RRT) or extracorporeal membrane oxygenation (ECMO)-related mortality among greater than or equal to 100 individual patients. DATA EXTRACTION:. Random-effects meta-analysis was used to generate pooled estimates of case fatality rates (CFRs) for in-hospital, ICU, MV, RRT, and ECMO-related mortality. ICU-related mortality was additionally analyzed by the study country of origin. Sensitivity analyses of CFR were assessed based on completeness of follow-up data, by year, and when only studies judged to be of high quality were included. DATA SYNTHESIS:. One hundred fifty-seven studies evaluating 948,309 patients were included. The CFR for in-hospital mortality, ICU mortality, MV, RRT, and ECMO were 25.9% (95% CI: 24.0–27.8%), 37.3% (95% CI: 34.6–40.1%), 51.6% (95% CI: 46.1–57.0%), 66.1% (95% CI: 59.7–72.2%), and 58.0% (95% CI: 46.9–68.9%), respectively. MV (52.7%, 95% CI: 47.5–58.0% vs 31.3%, 95% CI: 16.1–48.9%; p = 0.023) and RRT-related mortality (66.7%, 95% CI: 60.1–73.0% vs 50.3%, 95% CI: 42.4–58.2%; p = 0.003) decreased from 2020 to 2021. CONCLUSIONS:. We present updated estimates of CFR for patients hospitalized and requiring intensive care for the management of COVID-19. Although mortality remain high and varies considerably worldwide, we found the CFR in patients supported with MV significantly improved since 2020.